2016
DOI: 10.1039/c6en00232c
|View full text |Cite
|
Sign up to set email alerts
|

Combined experimental and computational approach to developing efficient photocatalysts based on Au/Pd–TiO2nanoparticles

Abstract: Quantitative structure–photocatalytic activity relationship modeling of surface modified TiO2-based nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 82 publications
0
31
1
Order By: Relevance
“…[1][2][3] Various strategies have been attempted to increase the visible light absorption of wide bandgap semiconductors such as doping with metal or nonmetal elements, 4-8 surface deposition of noble metals for plasmon effects, [9][10][11] and coupling with smaller bandgap semiconductors, 12-14 quantum dots 15,16 and dyes. [17][18][19] Among them, dye sensitization has been successfully demonstrated for many applications such as photocatalytic hydrogen production 20,21 and dye-sensitized solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Various strategies have been attempted to increase the visible light absorption of wide bandgap semiconductors such as doping with metal or nonmetal elements, 4-8 surface deposition of noble metals for plasmon effects, [9][10][11] and coupling with smaller bandgap semiconductors, 12-14 quantum dots 15,16 and dyes. [17][18][19] Among them, dye sensitization has been successfully demonstrated for many applications such as photocatalytic hydrogen production 20,21 and dye-sensitized solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several methods have been developed to remove malodors from the textiles, such as absorption/adsorption of odorous volatiles, [12][13][14][15][16] hot water or steam extraction, [17][18][19][20][21] and masking unpleasant odors through adding a fragrancecarrying compound to the surface or to the air. [22][23][24][25] However, these approaches only demonstrated limited efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…22 Nanotechnology may provide a better choice to address this issue. 20 Among them, an Engineered Water Nanostructures (EWNS) method, which is based on the conversion of atmospheric water vapor into EWNS by electrospraying, has attracted much attention recently. The EWNS technology was rstly reported by the Panasonic Group and the Harvard University in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Unmodified titania NPs are generally considered to be inert and non-toxic [ 3 ]. However, several studies have reported that TiO 2 nanomaterials may elicit toxic effects towards bacteria under UV light [ 4 ], which makes it possible to use them as an antibacterial material [ 5 6 ]. In TiO 2 -based nanoparticles, electron/hole (e − /h + ) pairs can be generated under UV light.…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, free radicals are produced, which is one of the major pathways of the antibacterial activity of TiO 2 -based NPs. In the absence of UV light, photoactive TiO 2 nanomaterials demonstrate little or no bacteria inhibiting activity [ 5 6 ]. Reactivity of TiO 2 under visible light (λ > 400 nm) can be achieved in several ways [ 7 ], including: (a) metal doping [ 8 ], (b) non-metal doping [ 9 10 ], (c) self-doping (reductive treatments) [ 11 12 ], (d) surface modification by noble-metal nanoparticles of silver (Ag), gold (Au), platinum (Pt), or palladium (Pd) [ 13 – 14 ], (e) the use of dye-modified TiO 2 [ 15 – 16 ], or (f) coupling TiO 2 with other semiconductors [ 17 18 ].…”
Section: Introductionmentioning
confidence: 99%